Expressão local de interferon alfa, dos receptores de interferon alfa (IFNAR) e da enzima 2´5´Oligoadenilato sintetase em pacientes com neoplasia intraepitelial cervical - TIRONE, Nelson Rannieri (2008)
Interferor-alfa (IFN-α) is a glicoprotein belonged to a family of cytokines which participate in the control and cell replication in the defence of hostess against strange organisms, as vírus or bacteria. Although the IFN-α has been known by antiviral property, numerous investigations afterward showed that the IFN is involved on regulation cell growth and on immunomodulatory effect. The IFN-α engage with the receptors of interferon alpha (IFNAR 1 and 2 ) with are expresses many types of cells of organism including growth cells and immune system. The synthesis of protein involved in intracellular resistance against vírus includes the production of 2.5. OAS. This enzyme binds with high affinity to RNase L and endoribonuclease that bunch the signs of single stranded of RNA taking the inhibition of viral proteins. In the literature there aren´t reports about evaluation of expression of genes receptors of interferon alpha and enzyme 2.,5. OAS in cells of cervical intraepithelial neoplasia wake up us to the intention of study and corelation themselves to expression of receivers, or a possible disfunction in translate of sign intracell, that consequence will take a minus ativation of enzyme, factors would be contribute to difficult the extintion of HPV or will act as a facilitator in evolution of epithelials cells to neoplasics injuries. The present work evaluated for RT-PCR the expression of mRNA of IFN-α, the receptors of Interferon alpha ( IFNAR 1 and IFNAR 2 ) and the expression of one of responsible elements encouragement of interferon ( ISRE ) to be present in regions of genes induced by IFN-α; through of the expression of mRNA of enzyme 2. 5. oligoadenilato synthetase ( 2.,5. OAS ) in biopsies of patients in different levels of cervical intraepithelial neoplasia ( CIN I, II and III ). Biopsies of uterine cervix was collected in women with CIN I, II and III ( n=28 ) and controls ( n= 17 ) without injury or infection by HPV. The presence of DNA of HPV with high and low risk was determined by hybrid capture. Levels of mRNA of IFNAR 1, IFNAR 2, IFN-α and 2.5.OAS were determined by RT-PCR. After the transcription the cDNA was submitted to amplification with specifics primers. In the research of expression of the interferon receptor alpha 1 ( IFNAR 1 ) the sample controls showed greater expression of the receptor 58,3% ( 10/17 ), while in the sample CIN 14,2% ( 4/28 ) expressed the mRNA of the receptor; p=0.0018. The expression of IFNAR2 was bigger also in the sample controls 64,7% ( 11/17 ) than in the patients with injuries 7,1% ( 2/28 ), p=0.0018. The simultaneous expression of two receptor was observed only in the control group 47,0% ( 8/17 ), p=0.0001. The results for the IFN-α show the presence of the fragment in 14,2% ( 4/28 ) of sample of CIN, without expression in the control group and the expression of levels of enzyme 2.5.OAS was 28,5% ( 8/28 ) in the samples of CIN and 11,7% ( 2/17 ) in the samples of control group, p=n.s. With the present study we can conclude that the samples of CIN showed the DNA of HPV in 50% ( 14/28 ), the samples have gotten of patients with cervical intraepithelial neoplasia showed one low expression of RNA messanger of the receptor of interferon subunit 1 and 2. The simultaneous expression of two subunits of receptors were found only in control group. There wasn.t significant difference of expression of RNA messanger of IFN-α and of enzyme 2.5.OAS between the control groups and CIN.